PENGARUH ATRIBUT PRODUK DAN SIKAP KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR HONDA PADA MAHASISWA UNIVERSITAS RIAU - Indah Ayu Lestari; Sri Kartikowati; Hardisem Syabrus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstack : The automotive industry is growing very rapidly in Indonesia, especially motorcycles. This condition makes consumers will be more selective in deciding to buy a brand of motorcycles. Purchasing decisions can be based on a variety of things including the product attributes and consumer attitudes toward the product. In choosing a product, consumers will be influenced by product attributes. Based on higher sales and a growing number of users Beat ESP Series as well as increased competition in product design attributes tribute to attract consumers. In this case, this study has the objective to determine the effect of product attributes and attitudes of consumers towards the purchase decision. This research is a quantitative research. The population is a student at the University of Riau with established criteria, then it is used a sample of 50 students with accidental sampling technique. Moreover, data and instruments is used primary data and questionnaire survey method. Data analysis technique used is descriptive analysis, classic assumption test and multiple linear regressions. The results obtained by analysis of product attributes and consumer attitudes or a significant positive influence on purchase decisions. From the results of research, the researcher suggested that firms increase or maintain product attributes in order to remain the top choice of consumers.Keywords : Decision Purchasing, Product Attributes, Consumer Attitudes